Rhabdomyosarcoma in children – current pathologic and molecular classification - Dziuba, Ireneusz; Kurzawa, Paweł; Dopierała, Michał; Larque, Ana B.; Januszkiewicz-Lewandowska, Danuta (Polish Journal of Pathology, 2018)
The last 25 years have brought significant progress in the treatment of sarcomas in children, especially rhabdomyosarcoma (RMS). Nevertheless, treatment failure in some patients results from considerable biological heterogeneity noted in these tumours. RMS, the most common malignant soft tissue neoplasm in children, includes two main subtypes: embryonal (ERMS) and alveolar (ARMS). Due to greater aggressiveness and worse prognosis of ARMS in comparison to ERMS, discrimination between different rhabdomyosarcoma subtypes is of crucial clinical importance. This paper presents the current histological classification of RMS, up-to-date immunohistochemical and biological research regarding RMS, and its associated clinical and prognostic significance.